226k views
0 votes
Which of the following equations could be used to solve the given equation?

9x + 26 + 7x - 17 = 2x + (-3x) + 5x

16x + 9 = 0
16x + 9 = 4x
16x + 11 = 4x

User JohnnyAW
by
5.5k points

2 Answers

2 votes
If we simplify like terms on left and right sides we gwt

16x + 9 = 4x

Its B
User Beardo
by
5.1k points
0 votes

Answer: The correct option is (B)
16x+9=4x.

Step-by-step explanation: We are given to select the correct equation that could be used to solve the following equation :


9x+26+7x-17=2x+(-3x)+5x~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)

To find the correct equation, we need to simplify the given equation (i).

From equation (i), we get


9x+26+7x-17=2x+(-3x)+5x\\\\\Rightarrow (9+7)x+(26-17)=2x-3x+5x\\\\\Rightarrow 16x+9=(2-3+5)x\\\\\Rightarrow 16x+9=4x.

Thus, the required equation is
16x+9=4x.

Option (B) is CORRECT.

User Stephannie
by
6.4k points